2022
DOI: 10.1039/d2cc02618j
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic water oxidation enabling the highly selective oxidation of styrene to benzaldehyde

Abstract: A reactive oxygen species mediated electrooxidation strategy is proposed to realize the transformation of styrene to benzaldehyde with high selectivity of ca. 89% and Faradaic efficiency of 28.8% on Pt...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Additionally, other active oxygen species generated from OER were studied in electrochemical oxidation. On a Pt anode, it was observed that styrene could be converted to benzaldehyde via ⋅OH and O 2 ⋅ − species, which were captured by radical scavengers and electron paramagnetic resonance (EPR) measurements [114] …”
Section: Electrochemical Oxidation Of Alkenes Using H2o As Oxygen Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, other active oxygen species generated from OER were studied in electrochemical oxidation. On a Pt anode, it was observed that styrene could be converted to benzaldehyde via ⋅OH and O 2 ⋅ − species, which were captured by radical scavengers and electron paramagnetic resonance (EPR) measurements [114] …”
Section: Electrochemical Oxidation Of Alkenes Using H2o As Oxygen Sourcementioning
confidence: 99%
“…On a Pt anode, it was observed that styrene could be converted to benzaldehyde via * OH and O 2 *À species, which were captured by radical scavengers and electron paramagnetic resonance (EPR) measurements. [114] Apparently, the understanding of reaction pathway at molecular level is still elusive, despite of extensive research on the electro-oxidation of olefins. To further optimize the efficiency, including the design of anodic catalysts, electrolytes, and cells, more efforts need to be devoted to the mechanism analysis and establishment of structure-activity relationships.…”
Section: Heterogeneous Catalysts For Other Oxygenating Reactions Of A...mentioning
confidence: 99%
“…The synthetically relevant reactions developed in this context include the lactonization of ketones, 4 epoxidation of alkenes, [5][6][7][8] oxidation of suldes 9,10 and oxidation of C-H and C]C bonds to carbonyls. 11,12 Developing electrochemical oxygen-atom functionalization reactions with water serving as the oxygen source requires solubilization/dispersion of both the organic substrate and water, which are generally immiscible. This can be achieved by the use of multiphasic or monophasic electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetically relevant reactions developed in this context include the lactonization of ketones, 4 epoxidation of alkenes, 5–8 oxidation of sulfides 9,10 and oxidation of C–H and CC bonds to carbonyls. 11,12…”
Section: Introductionmentioning
confidence: 99%